Deepening responses associated with improved progression-free survival with ixazomib versus placebo as posttransplant maintenance in multiple myeloma - Goldschmidt, Hartmut; Dimopoulos, Meletios A.; Rajkumar, S. Vincent; Weisel, Katja; Moreau, Philippe; Chng, Wee Joo; Mikala, Gábor; Cavo, Michele; Ramasamy, Karthik; Suryanarayan, Kaveri; Teng, Zhaoyang; Labotka, Richard; et al. (Leukemia, 2020)
In the TOURMALINE-MM3 study, post-autologous stem cell transplantation maintenance therapy with the oral proteasome inhibitor ixazomib versus placebo significantly improved progression-free survival (PFS), with a favorable safety profile. With ixazomib versus placebo maintenance, deepening responses occurred in 139/302 (46%) versus 60/187 (32%) patients with very good partial response or partial response (VGPR/PR) at study entry (relative risk 1.41, P = 0.004), and median time to best confirmed deepened response was 19.9 versus 30.8 months (24-month rate: 54.2 versus 41.4%; hazard ratio (HR): 1.384; P = 0.0342). Median PFS in patients with VGPR/PR at study entry was 26.2 versus 18.5 months (HR: 0.636, P < 0.001) with ixazomib versus placebo; in a pooled analysis across arms, in patients with versus without deepening responses, the median PFS was not reached versus 15.9 months (HR: 0.245, P < 0.001). In patients with deepening responses, 24-month PFS rate was 77.4 versus 68.3% with ixazomib versus placebo (HR: 0.831; P = 0.466); in patients without deepening responses, median PFS was 17.9 versus 14.1 months (HR: 0.741; P = 0.028). These analyses demonstrate the significantly higher rate of deepening responses with ixazomib versus placebo maintenance and the association between deepening response and prolonged PFS.